Legal Problematics Differences in Land & Building Transactions with Validation of Cost of Obtaining Rights to Land & Building (Perda No. 2 of 2011 In Kendari City) - Andi Nurul Chaerunnisa (Program Studi Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam SUltan Agung, 2020)
Tax is one of the largest revenues from the State of Indonesia, in this case one of the results of tax collection is the tax on the acquisition of rights to structures and buildings (BPHTB). the existence of regional autonomy, collection of fees for the acquisition of land rights andthis building is collected by each region independently. The issuance of Act No. 28 of 2009 concerning local taxes and levies made Kendari city regions issue regulations related to local taxes. It is Kendari city regional regulation No. 02 of 2011 regarding local taxes. The amount of collection of fees for acquisition of land and building rights is 5% (five percent) of the value of the acquisition of tax objects (NPOP), this is stated in Article 54. Meanwhile, the collection of fees for the acquisition of rights to land and buildings is carried out by the regional revenue agency. This study aims to determine the determination of the transaction value as the basis for BPHTB validation by the Bapenda of Kendari and to find out legal problems that can arise due to differences in actual transaction prices with BPHTB verification by the Bapenda of Kendari. The method taken by the author is a normative method. The normative approach is an approach that is carried out based on the main legal material by examining theories, concepts, legal principles and laws and regulations.